Inclusive Entrepreneurship Education for National Development: Implication for Educational Administration in Nigeria - Akpama, Ada Mary Juliana; Eneji, Theresa &; Ogar, Chris-Valentine (International Journal of Psychosocial Rehabilitation, 2020)
–The paper examines inclusion and entrepreneurship in the Nigerian educational system. It identifies inclusive entrepreneurship education as a pivot to the achievements of Nigerian educational objectives as well as the attainment of the desire for adequate skilled manpower development for national development, especially in the fight to eradicate poverty. The paper explained the concepts of inclusive education, the nexus between inclusive education and entrepreneurship education, the association between entrepreneurial education in inclusive setting and the impact this has for the achievement of national development. It stressed on the significance of inclusive entrepreneurship education for national development especially among people with disabilities’; noting the cycle between disability and poverty. The descriptive survey research design was used, a sample of three hundred respondents were selected from among lecturers and postgraduate students in the departments of Vocational Education, Special Education, Educational Administration and Planning and Entrepreneurship Center in the University of Calabar, Nigeria. Structured questionnaire was used for data collection, administered by the researchers and same collected. Pearson Product Moment Correlation and one way Analysis of Variance (ANOVA) was used for data analyses. The hypothesis of no relationship between inclusive entrepreneurship education and national development was significant at 0.05 significant levels and 298 degree of freedom, while out of the six roles educational administrators can play as listed, five were significant, while one was not significant at 0.05 significant level and degree o freedom 290. The study concluded that inclusive entrepreneurship education can provide the needed entrepreneurship skilled manpower development and contribute to national development, while educational administrators have very significant roles to play in the attainment of inclusive education in Nigeria. It was recommended that efforts should be geared urgently towards designing and implementing inclusive entrepreneurship education in Nigerian school curriculum.